Case Report and Literature Review: Clinical Characteristics of 10 Children With Mycoplasma pneumoniae-Induced Rash and Mucositis - Chen, Ning; Li, Miao (Frontiers in Pediatrics, 2022)
Mycoplasma pneumoniae-induced rash and mucositis (MIRM) is a rare disease, which has not been reported in northern China previously. We retrospectively analyzed the clinical characteristics, diagnosis and treatment of 10 cases of MIRM in order to help clinicians to identify MIRM and to distinguish it from the similar mucositis and cutaneous characteristics of Stevens-Johnson syndrome. All 10 children included in the study had MIRM with skin and mucosal symptoms, but the characteristics of the skin and mucosal lesions differed by age. Most of the older children had sparse erythema and a vesicular rash, but the younger children had dense erythema without blisters but with purulent exudation. The mucositis was relatively mild in the younger children. The erythrocyte sedimentation rate, the levels of C-reactive protein, lactate dehydrogenase, and D-dimer were significantly elevated in most children with MIRM. Concomitant treatment of glucocorticoids and/or IVIG with macrolides may shorten the duration of fever and accelerate the clinical recovery. Additional case reports are needed to improve knowledge of the characteristics of MIRM and its response to therapy.